Identification and Characterization of Indole and Oxindole Alkaloids from Leaves of Mitragyna speciosa Korth Using Liquid Chromatography–Accurate QToF Mass Spectrometry. (27th November 2019) - Avula, Bharathi; Sagi, Satyanarayanaraju; Wang, Yan-Hong; Wang, Mei; Ali, Zulfiqar; Smillie, Troy J; Zweigenbaum, Jerry; Khan, Ikhlas A
Abstract: Alkaloids have been reported to be the major physiologically active constituents in Mitragyna . An analytical method was developed to provide an alternative, fast method for characterization of alkaloids from various M. speciosa samples. The separation was achieved using an RP octylsilyl (C8) column, MS detection, and a water–acetonitrile with formic acid gradient as the mobile phase. Ultra-HPLC/quadrupole time-of-flight MS analysis and characterization were performed on 12 corynanthe-type indole/oxindole alkaloids obtainedfrom the leaves of M. speciosa Korth. The indoles and oxindoles had an open E ring withor without substitution occurring at the C9 position. The full single mass spectrum of alkaloids showed a strong signal for the protonated molecule [M+H] + . The product ion spectrum of mitragynine type of alkaloids showed strong response at m / z = 174.0901 suggestive of an ion containing an odd number of nitrogen atoms corresponding to formula C11 H12 NO, which is characteristic of indole alkaloids. A multivariate statistical analysis technique, principal component analysis, was used to show discrimination between the M. speciosa samples.The results indicated that the analytical method is suitable for QC testing of various Mitragyna commercial samples and can be used to evaluate market products purported to contain M.speciosa .